Course Development: Integrated Design, Manufacturing and Testing. Issue 1 (January 2014) - Adair, D.; Jaeger, M.
This paper discusses a course developed to give first-year mechanical students insight into a typical process found in professional modern design offices, where requirements (specifications) are evolved into a prototype model whose capabilities are then tested. The intent is to provide the participating students with a hands-on, integrative, multifaceted experience in the important field of mechanical engineering design. Topics addressed include Integrated Product Design, Rapid Prototyping and Product Testing, and here, the careful design and development of the course is discussed, as is the assessment process. The experiences and views of the students taking the course are reflected using questionnaire-style surveys.